If it's not what You are looking for type in the equation solver your own equation and let us solve it.
f(1)=10
We simplify the equation to the form, which is simple to understand
f(1)=10
Reorder the terms in parentheses
+(+1f)=10
Remove unnecessary parentheses
+1f=+10
We move all terms containing f to the left and all other terms to the right.
+1f=+10
We simplify left and right side of the equation.
+1f=+10
We divide both sides of the equation by 1 to get f.
f=10
| y=5+-13 | | (9m+10).2= | | -7y+28=-3(5y+4) | | (x-(1+2i))(x-(1-2i))=0 | | 2y+3=9+6y | | 15x^2+5-[5(x^2-7)+9]= | | 5p^2=300+20p | | 2x-1+2x=4x+28 | | -6=-5 | | -31+6x=-1-3(-5x+1) | | 4k^3w+20k^2w^2+25kw^3=0 | | 4(6x^2-7)-[6(3x^2-4)+3]= | | 5n+3(n+a)=28 | | lx(x+8)+ln(x-1)=2lnx | | 7-2(4r+3)=-6 | | 3(4-x)=10+2x | | 2w^2-4w-70=0 | | 67-b=49 | | 4(7-2n)+4n=-5n+34 | | A=650-8(75) | | -3z^2+2z-35=0 | | y=0.5+4 | | -8c=24 | | 3ax(7xa)= | | 0.04(x^3+125)+2=14-x | | 7(x+4)=7 | | (4x-16)(4x-16)-(x-2)(x-2)=(8-x)(8-x) | | 16x+27=15x+19 | | -q=6 | | -8+2=26 | | 5x^2-21x=18 | | 7x+2=6x-2 |